The Jensen project - Barr, Douglas, 1949-; Martin, Kellie, 1975-; Smith, Brady; Burton, LeVar; Kelly, Justin; Diaz, Alyssa; Andrews, David, 1952-; Richardson, Patricia, 1951-; Jackson, Randy; Allaman, Eric.; Wal-Mart (Firm) ([United States] : PGP, 2010)
A community of brilliant scientists known as the Jensen Project team up with two former Project members and their genius teenage son to prevent dangerous technology from falling into the wrong hands.
CD soundtrack. Don't stop / Randy and the Jensen All-Stars -- One step at a time / Jordin Sparks -- Feel / the Less -- All is well / Warren Barfield -- Soul / Paper Tongues -- Don't keep me here waiting / Justin York -- Anything is possible / Steven Manuel -- Sweet nothing / Ashlyne Huff -- Be the one / Alisan, Isley, & Jordan -- Take it away / Brooke White -- Everything that is real / Jillian Edwards -- Elevate / Twin.
"CD soundtrack by Randy Jackson"--Container.
Originally produced for television in 2010.
Special features: Beyond the Jensen Project.
Music, Randy Jackson, Eric Allaman ; editor, Simon Webb ; production designer, Zoe Sakellaropoulo ; director of photography, Pierre Jodoin.
Audio CD credits: executive producer, Randy Jackson ; mastered by Stephen Marcussen at Marcussen Mastering, Hollywood, Calif.
Kellie Martin, Brady Smith, LeVar Burton, Justin Kelly, Alyssa Diaz, David Andrews, Patricia Richardson.
Keywords: Scientists -- Drama; Gifted persons -- Drama; Gifted teenagers -- Drama; Nanotechnology -- Drama; Science fiction films; Made-for-TV movies; Motion picture music